Applications of Laplace Homotopy Analysis Method for Solving Fractional Heat-And Wave-like Equations (Global Journal of Science Frontier Research, 2012)
In this paper, we apply Laplace homotopy analysis method for solving various fractional heat-and wave-like equations. This method is combined form of homotopy analysis method and Laplace transform. The proposed algorithm presents a procedure of construct the base function and gives a high order deformation equation in simple form. The purpose of using the Laplace transform is to overcome the deficiency that is mainly caused by unsatisfied conditions in the other analytical techniques. Numerical examples demonstrate the capability of LHAM for fractional partial differential equations.
Keywords: Laplace homotopy analysis method; homotopy analysis method; fractional heat- and wave-like equations